Edukasi Pentingnya Bakteri Asam Laktat (BAL) Terhadap Kesehatan Saluran Cerna Bayi - Suci Rahmani Nurita; Tuhu Perwitasari (Jurnal Abdimas Kesehatan (JAK), 2021)
Infant Mortality Rate is one indicator that determines health status. Every year there are 3 million infant deaths in the world, 80% of which occur in the first 6 days of life, with pneumonia and diarrhea still being the main causes of death. Based on Nurita's research (2019) on postpartum mothers and newborns, which aims to determine the relationship between the frequency of giving colostrum and birth mode with the number of Lactic Acid Bacteria (LAB) colonies in the neonatal gastrointestinal tract. The results of the study found that the number of LAB colonies in babies born vaginally and C-Section was not much different, but the number of LAB colonies would increase in number if breast milk was often given. The education carried out targets an increase in the knowledge of educational participants with the outputs in the form of informative leaflets, educational video, educational X-Banners, activity reports and journal publications. Community service activities begin with licensing arrangements, time contracts, preparation of educational tools and materials, visits to Independent Midwives Practice (PMB, explanations of educational materials, discussions and questions-answers, showing educational videos, and handing over Educational X-Banners. It can be concluded that educational participants are still unfamiliar with lactic acid bacteria (LAB) and their role in the health of the baby's gastrointestinal tract, so further education is needed